Effectiveness of smartphone otoscope in management of ear ailments at primary healthcare level - Shyamlal, Yadav Sagar; Bhatnagar, Akshay; Oberoi, Anant; Gianchand, Shikha (International Journal Of Community Medicine And Public Health, 2023)
Background: To work out efficacy of smartphone otoscope for managing ear ailments at primary healthcare level. Methods: Prospective study carried out at a co-located primary care clinic and secondary referral facility. With this plan, the PHC was equipped with a smartphone otoscope for diagnosing common ear problems. The doctor then forwarded patient's ear imaging to the referring hospital's otolaryngologist. The otolaryngologist reviewed the history to make remote diagnosis before providing the PHC provider with recommendations for treatment. Information on patients' demographics, outpatient diagnoses, symptom durations, affected side, treatments received, and outcomes was collected. This information was used to determine whether or not a smartphone otoscope may be used to improve healthcare for patients suffering from common ear illnesses without sending them to more specialized facilities. Results: 150 patients were enrolled; 53.3% were male and 46.7% female. Participants aged between 3 and 83 years, with a mean of 44.6. Eighty-two (48%) of the cases presented with left ear, sixty (40%) with right ear, and eighteen (12%) for both sides. The typical course of ear infection lasted 6.5 (2, 15) days. Out of 150 patients, 33 (22%) were deemed cured, 117 (78%) demonstrated improvement in symptoms. The technique was praised by primary care physicians, who said they learned more about otolaryngology. Conclusions: The ability of primary care physicians to manage common and straightforward ear ailments is greatly enhanced by the use of smartphone otoscopes. Thus, improving patient satisfaction and the strain on medical facilities.